Low-temperature deposition of silicon dioxide films in high-density plasma - Yasunas, A.; Kotov, D.; Shiripov, V.; Radzionay, U. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
One of the basic operations in the LED (light-emitting diode) chip fabrication
technique is formation of dielectric coatings for the purpose of insulation and surface
passivation of the LED structure. Oxides and nitrides of silicon obtained by physical or
chemical vapor deposition techniques can act as such a coating. Low conformity of
physical vapor deposition techniques limits the possibility of their application in a
number of cases at LED mesostructures passivation. This work represents the results of
experiments on silicon dioxide dielectric films deposition in the inductive coupled
plasma under different operation conditions. The findings prove the possibility of lowtemperature
deposition of thick silicon dioxide films with high conformality by the
HDPCVD (high-density plasma chemical vapor deposition) technique.